Characteristics of parents with shared residence and father sole custody. Evidence from Norway 2012 - Ragni Hege Kitterød; Jan Lyngstad (Statistics Norway, Research Department, 2014)
Shared residence for children has increased considerably in recent years among parents living apart in Norway, while mother sole custody is less common than before and father sole custody is still practiced by a minority. A similar pattern is observed in many other countries as well. In Norway, 25 prcent of the parents with separate homes now practice shared residence for their children, compared to only 10 percent in 2004. Such an arrangement is most common among highly educated parents, those who have been married or cohabiting for a long rather than a short time, when the parents shared childcare tasks equally between themselves when they lived together, and when neither parent has problems with household finances. Father sole custody is practiced by only 10 percent of the parents living apart. Such an arrangement is particularly common when the mother has health limitations or financial problems, when the father has no financial problems and when the parents divided childcare activities equally between themselves before they split up.
Keywords: J11; J12; J13; J18; 330; Contemporary families; Father sole custody; Mother sole custody; parents living apart; shared residence